Reproductive Health: Health Education to Improve Knowledge in Adolescent Girls - Suhartin Haringi; Arfina Yusuf; Waode Ikrawati (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2025)
Reproductive health refers to a condition in which the reproductive process functions optimally and remains in a healthy state, encompassing physical, mental, and social well-being. It relates to the reproductive system, its functions, and the reproductive roles of adolescents. Adolescence is a crucial stage of human development, characterized by the onset of puberty and the attainment of sexual and reproductive maturity. During this period, adolescents face various physical and psychological changes that require adequate knowledge to support healthy behavior. Health education plays an essential role in improving adolescent girls’ understanding of reproductive health. This study aimed to enhance knowledge and awareness regarding reproductive health among teenage girls through structured health education interventions. The program was implemented over three weeks, utilizing face-to-face counseling sessions in conjunction with the distribution of informative posters. Counseling sessions provided opportunities for direct interaction, allowing participants to clarify misconceptions and receive accurate information, while posters served as visual reminders to reinforce key messages. The results of the intervention demonstrated a noticeable increase in adolescent girls’ knowledge and awareness of reproductive health, including the potential risks of sexual deviations and behaviors that could negatively impact their well-being and their families. This educational approach not only improved their understanding of reproductive health but also encouraged the development of responsible attitudes and preventive behaviors. Promoting reproductive health education for adolescents is essential in fostering a healthy transition into adulthood and reducing the likelihood of reproductive health issues in the future.